Gender-related differences in cardiometabolic risk factors and lifestyle behaviors in treatment-seeking adolescents with severe obesity - Lisa Ha Barstad; Pétur B. Júlíusson; Line Kristin Johnson; Jens Kristoffer Hertel; Samira Lekhal; Jøran Hjelmesæth (BMC, 2018)
Abstract Background Obesity during adolescence is associated with cardiovascular mortality in adulthood. The adverse obesity-related cardiometabolic risk profile is already observed in adolescence. We aimed to examine possible gender differences in cardiometabolic risk factors and lifestyle behaviors among adolescents with severe obesity, hypothesizing that boys would have both a higher prevalence of the metabolic syndrome as well as less healthy lifestyle behaviors than girls. Methods Cross-sectional study of treatment-seeking adolescents with severe obesity who attended the Morbid Obesity Centre at Vestfold Hospital Trust and who were consecutively enrolled in the Vestfold Register of Obese Children between September 2009 and September 2015. A total of 313 adolescents aged 12 to 18 years were recruited, whereof 268 subjects (49% boys) completed a food and activity frequency questionnaire and were included in the analysis. Results Mean (SD) age, BMI and BMI SDS were 15 (1.6) years, 38.6 (5.9) kg/m2 and 3.5 (0.6). Levels of LDL cholesterol, fasting insulin and glucose and diastolic blood pressure (DBP) did not differ between genders. Compared to girls, boys had significantly higher triglycerides (p = 0.037) and systolic blood pressure (SBP) (p = 0.003), as well as lower HDL cholesterol (p = 0.002). The metabolic syndrome was present in 27% of the boys and 19% of the girls (p = 0.140), and the prevalence of high DBP, dyslipidemia and dysglycemia also did not differ significantly between genders. The prevalence of high SBP was higher in boys than in girls (19% vs. 9%, p = 0.021). Gender was associated with a number of lifestyle habits, as a larger proportions of boys had higher screen time (p = 0.032), more regular breakfast eating (p = 0.023), higher intake of sugar sweetened soda (p = 0.036), and lower intake of vegetables than girls (p = 0.011). By contrast, physical activity level and intake of fruit and berries did not differ between genders. Conclusions Male treatment-seeking adolescents with severe obesity had a more unfavorable set of metabolic and behavioral risk factors for cardiovascular disease than girls. Our results indicate that lifestyle behavioral markers should be thoroughly assessed in both genders, and possible gender-related differences in risk profile should be taken into account in future treatment programs.